If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7m + -3 = 9m + 6 + -1m Reorder the terms: -3 + 7m = 9m + 6 + -1m Reorder the terms: -3 + 7m = 6 + 9m + -1m Combine like terms: 9m + -1m = 8m -3 + 7m = 6 + 8m Solving -3 + 7m = 6 + 8m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-8m' to each side of the equation. -3 + 7m + -8m = 6 + 8m + -8m Combine like terms: 7m + -8m = -1m -3 + -1m = 6 + 8m + -8m Combine like terms: 8m + -8m = 0 -3 + -1m = 6 + 0 -3 + -1m = 6 Add '3' to each side of the equation. -3 + 3 + -1m = 6 + 3 Combine like terms: -3 + 3 = 0 0 + -1m = 6 + 3 -1m = 6 + 3 Combine like terms: 6 + 3 = 9 -1m = 9 Divide each side by '-1'. m = -9 Simplifying m = -9
| -85+3x=83-9x | | (5x-3)+(n+9)=24 | | X^3+13x^2=0 | | 6y+4=6y-9 | | 16(z+3)=4(z-9) | | (2x-4)(x+3)= | | 2a-4b=58 | | -a+5=5a+5 | | 3x-7=-3 | | F(5)=20x+11 | | 4x^3+8x^2+3x+6=0 | | q-rb=15a | | 2x+12i=3y+2yi | | 12p=p+24+p | | 18x^2+45x+15=-10 | | 2w+9=-3 | | 2m+5=m+4 | | sin(10x)*cos(5x)=0 | | 3(x^2-10)-3x=6(x^2-2x) | | 4(y+4)+3=39 | | (8y+13)(5y+24)=0 | | (4x+4)(8x+10)=0 | | 9=3-a | | 6h+5+h=-3 | | 2x^3-12x-32x-192=0 | | x-3=-3x-23 | | 10t-4= | | -4x+3=6x+23 | | 3x-4x=-4x-11 | | 8+4m=-12 | | 8g=10+6g | | 9y=1800 |